EVALUASI PENGENDALIAN WAKTU DAN BIAYA PADA PROYEK KONSTRUKSI MENGGUNAKAN METODE EARNED VALUE ANALYSIS (EVA): (Studi Kasus Pada Proyek Rekonstruksi Jalan Cikupa – Putra Raja Kecamatan Pamarican Kabupaten Ciamis) - Khoerunnisa, Rina Nurul; Maskur, Atep; Hartati, Gini (Jurnal Ilmiah Teknik Sipil, 2025)
Construction projects often face problems related to the time and cost aspects of their implementation, which lead to irregularities in the form of delays in completion times and cost overruns, this condition indicates the need for the implementation of an effective control system. The Cikupa – Putra Raja road reconstruction project, Pamarican District, Ciamis Regency experienced deviations or delays from the planned schedule in the early stages of its implementation. So this study aims to determine time and cost control using the Earned Value Analysis method to evaluate the performance of project implementation. This study uses a quantitative descriptive method by analyzing secondary data obtained from project documents, including Cost Budget Plan, time schedule, and project weekly reports. The results of the study show that the project was completed according to the schedule and budget plan, namely in 90 days with an actual cost of IDR 2,499,185,000.00. This is indicated by an average positive Schedule Variance value and a Schedule Performance Index value (SPI > 1), this means that the schedule performance is good. From the cost aspect, the average Cost Variance value is positive and the Cost Performance Index value (CPI = 1), indicating that the cost expenditure is in accordance with the budget. Despite delays in the planning schedule in the early stages of its implementation, the project can be controlled without any time and cost. These findings show that the Earned Value Analysis method is effective in controlling and evaluating project performance.